Relationship Dimension In University Laboratories And Its Effects On Students’ Interest - Rosdi, Atiqurrahman; Ilham, Zul; Azizan, Suzana Ariff; Zulkefeli, Mohd; Saifuddeen, Shaikh Mohd (Future Academy, 2018)
Malaysian universities are currently facing a decline of students’ interest in science. It is perceived that the students’ practices in laboratory activities with properly managed activities could result in positive interest in science. In that sense, it is argued that laboratory activities are less constrained, creating excellent opportunities for the interaction between instructor and students to occur. Hence, this study was aimed to examine the relationship dimension in university laboratories and its’ connection towards the students’ interest in a science subject. Drawing upon a survey conducted over 321 science students in four Malaysian Universities, a series of exploratory factorial, descriptive and regression analyses were applied in this study context. The results proved that in the aspects of instructor supportiveness, student cohesiveness and involvement explained 56.15% of the variations and exhibited a positive relationship with the students’ interest in science. Subsequent analysis also found that both instructor supportiveness and student cohesiveness demonstrated significant contributions of 17.2%. The relationship dimension definitely showed significant contribution although in small percentages. As the laboratory objectives are ultimately important to achieve, future research should examine the best practices in laboratory to develop students’ interest in science.